Kikuchi-Fujimoto Disease (Medical Journal of Indonesia, 2005)
Kikuchi-Fujintoto disease (KFD) was first reported by 2 Japanese pathologists, Kikuchi and Fujimoto, independently in 1972. KFD is an idiopathic, self-limited necrotizing lymphadenitis. The most common clinical manifestation is cervical lymphadenopathy accompanied by fever, myalgia, leukopenia, and skin rash. The purpose of this paper is to report the first case of Kikuchi-Fujimoto disease in a twelve year old girl in Dr.Cipto Mangunkusumo Hospital. Jakarta. (Med J Indones 2005; 14: 107-12) Keywords : Cervical limphadenopathy, self-limited necrotizing lymphadenitis